Medication options in the treatment of cutaneous american tegumentary leishmaniasis - Miranda, Carolina Galgane Lage; Cardoso, Jean Matheus Guedes; Alcântara, Lucas Oliveira Nepomuceno de; Santos, Leandra de Cássia Ribeiro dos; Dutra, Ana Luisa Valcanaia; Carvalho, Filipe Oliveira Ferrolho de; Rocha, Lucas de Almeida; Guedes, Ana Beatriz Gonçalves de Sousa; Aniszewski, Rayssa Victoria Lima; Soares, Paulo Augusto Borges; Felipe, Ana Luísa Gonçalves (Seven Editora, 2024)
American cutaneous leishmaniasis is an infectious disease endemic in about 100 countries, with three predominant forms: cutaneous, mucosal and visceral. It is classically transmitted by the bite of the Lutzomyia mosquito and, after infection, occurs with the formation of a papular lesion, which evolves to the formation of a nodule, and may even be associated with regional adenopathy. Cutaneous leishmaniasis (CL) deserves special attention because it is the most recurrent presentation of ATL, subdivided into two forms: localized and disseminated. The diagnosis of ACL comprises the association of the clinical history with the local epidemiological profile, associated with laboratory tests that prove the presence of Leishmania.  The complementary tests of choice are: histopathological, which reveals the presence of amastigote in tissue; the isolation of the parasite in an in vitro culture medium and the detection of parasite DNA by means of Polymerase Chain Reaction (PCR) examination. Regarding the treatment of this pathology, the main focus of this work, there are drugs under development and other drugs of already established use, such as: pentavalent antimonials, liposomal amphotericin B or deoxycholate, in addition to pentamidine, which belongs to aromatic diamines and is used for treatment in regions of the American, Asian and African continents. Therefore, when considering the impact that ACL can have on human quality of life, it is necessary to list the main drugs used in its treatment, in order to compare them and list the most effective and safe options. Therefore, a systematic literature review was carried out, in which research and scientific papers published in the last 10 years (January 2014 - January 2024) were evaluated in detail, in the PubMed bibliographic databases and in the Latin American and Caribbean Health Sciences Literature (LILACS). Thus, it will be possible to analyze which therapeutic options are available on the market, in addition to mentioning the new drugs under development, especially in order to minimize the side effects of the drugs in use. DOI:https://doi.org/10.56238/sevened2024.007-072